Determinants of healthcare utilisation among the elderly in Malaysia - Mohamad Yunus, Noor'ain; Abd. Manaf, Noor Hazilah; Omar, Azura; Juhdi, Nurita; Omar, Mohamed Azahadi; Salleh, Mohmad (University of Malaya, 2017)
Population ageing is pervasive, a global phenomenon and has implications for society and the nation. Among them is demand for greater allocation of financial resources for healthcare services to cope with this demographic trend. Therefore, this study was aimed at investigating the determinants of utilisation of healthcare services among the elderly in Malaysia. A questionnaire survey was conducted among those aged 60 in 14 public hospitals in Peninsular Malaysia. Findings revealed that age, education level, income level and need for care were associated with healthcare utilisation. Thus, this study contributed to a greater understanding of the determinants of healthcare utilisation among the elderly in Malaysia. Understanding these associations may help healthcare providers and policy makers design strategies to enhance the quality of healthcare services for the elderly.